ANALISIS KUALITAS WEBSITE MENGGUNAKAN MODEL WEBQUAL 4.0 (STUDI KASUS: WEBSITE SPEKMA UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI BOJONEGORO) - Ananda Devi Muri Utomo; Arista Pratama, Erista Maya Safitri (ADISAM PUBLISHER, 2023)
The increasingly rapid development of information and communication technology has had quite a positive impact on the world of education, especially in the learning process. The use of information and communication technology (ICT) can be carried out in various fields, one of which is the world of education in higher education. The implementation of ICT in higher education in the form of information systems can be a factor in success and progress in higher education, one of which is the proof of this is the student credit point website. In this study, researchers wanted to analyze the quality of the Student Credit Points website using the webqual 4.0 model. The webqual model is widely used to measure website quality based on end user perceptions. The results of this research, based on the results of the analysis, can be seen through calculating the level of suitability and the results of Cartesian diagram processing obtained on the usability variable with an average of 98.02% and the lowest value on the U6 indicator, namely 97.52%, while the highest value on the U8 indicator is 112.23. %. Meanwhile, for the information quality variable, results were obtained with an average of 97.04% and the lowest value for the IQ1 indicator was 96.13%, while the highest value for the IQ2 indicator was 101.59%. Meanwhile, for the Service interaction quality variable, results were obtained with an average of 102.07%, the lowest value was on the SIQ3 indicator, namely 97.58%, while the highest value was on the SIQ2 indicator, namely 104.93%